High performance Spanish athletes body composition estimation - Pons, V.; Riera, J.; Vela, J. M.; Ruiz, O.; Banquells, M.; Galilea, P. A.; Drobnic, F. (Archivos de medicina del deporte, 2008)
The aim of this work is to present the anthropometric data of a large sample of athletes collected from 1990 to 2008 at the Olympic Training Center of Sant Cugat del Vallés (CAR), to contribute to somatic references of elite Spanish athletes. Rules and technique used are recommended by the "International Working Group of Kinanthropometry" (Ross & Marfell-Jones, 1982), proposed by "International Society for the Advancement of Kinanthropometry" (ISAK) and by the "Grupo Español de Cineantropometría (GREC)". We have carried out 3475 anthropometries, 2294 males (21,3 +/-4,9 years) and 1181 females (19.7 +/-4,2 years) corresponding to 30 different sports. For the analysis we have selected those sports were the sample is representative, by the sample size or by his homogeneity and organized by sport and category. All necessary anthropometrics measurements were used to calculate body mass index (BMI), somatotype (Heath Carter), delta 6 skinfolds and percentage of fat (Yuhasz, Faulkner, Drinkwater). The data were expressed as means +/- SE. In the next graphic and table, we present some results of somatotype for athletics (Figure 1) We conclude that kinanthropometry data provides a clear appraisal of structural status at any given time, for quantification of different sports modalities and training influences. The knowledge of kinanthropometry normative data of elite athletes is a useful and necessary information for the professionals sports